Strategy for Strengthening Community Participation and Digitalization of Red and White Cooperative Governance in Sukabumi City - Siti Hodijah; Taqia Nurifqia; Siska Sri Mutiara; Utami Fadhilah; Tiara Siti Maspupah; Muhammad Dzikra Fawaz; Wildan Wildan; Mia Reviyona; Miftah Amir; Indra Putu Desa Nota (Siber Nusantara of Community Service Review, 2026)
This research aims to strengthen community participation and implement digitalization in the governance of the Red and White Cooperative (KMP) in Sukabumi City. The method used is a participatory approach by involving lecturers as supervisors and students as facilitators through legality counseling activities, managerial workshops, and intensive field assistance that includes door-to-door interaction for information system activation and curation of member products. The results of the study showed a significant increase in the participation and digital literacy of cooperative members, with an increase in the understanding of collective benefits by 56%, trust in the management by 61%, and digital report literacy by 63%. Digitization and information disclosure have succeeded in reducing the apathy of citizens, strengthening trust, and encouraging the development of cooperative productive business units. This program proves that the integration of persuasive education and digital technology is the main key in restoring the dignity of urban cooperatives and encouraging economic independence.